Use of shower: The effect on welfare and carcass and meat quality of pigs transported to slaughter - Dalla Costa, O. A.; Diesel, T. A. [UNESP]; Costa, M. J.R.P. [UNESP]; Dalla Costa, F. A. [UNESP] (My University, 2015)
This study was carried out to evaluate the effects of a shower before and after pig transportation on welfare, meat and carcass quality. We used 384 crossbreeding animals (females and castrated males), from 16 farms in Santa Catarina State, Brazil. A 2x4 factorial arrangement of treatments was employed with two distances from farm to slaughter plant (less than 50km and more than 50km) and four showering protocols. These protocols were applied on pigs: no showering at farm or slaughter plant (Control), no showering at farm but showering at the plant (NMG_MOF); showering at the farm and no showering at the plant (MOG_NMF); showering at the farm and plant (MOG_MOF). None of the factors influenced (P>0.05) physiological variables related to stress (cortisol and lactate in blood samples), number of carcass lesions and the characteristics of meat quality.